An improved seven-level switched-capacitor-based neutral-point clamped inverter - Kakar, Saifullah; Arif, M. Saad Bin; Ayob, Shahrin Md.; Nordin, Norjulia B. M.; Mekhilef, Saad; Seyedmahmoudian, Mehdi; Stojcevski, Alex (Frontiers in Energy Research, 2022)
Multilevel inverters (MLIs) have seen significant growth in a variety of medium- to high-power industrial applications and have become a mature and viable solution for renewable energy systems (RES) over the past decade. The major concerns of MLIs are the high component count and also the buck-type feature of the ac output voltage when used for grid-connected renewable-energy-based sources such as solar photovoltaic (PV) panels. Alternatively, a switched-capacitor (SC) based invert-er possessing the feature of boost ability is a prime solution to meet the requirements of ac power applications. Integrating an SC network with the neutral-point clamped (NPC) structure makes leakage current alleviation viable for transformerless PV grid-connected systems. In this paper, an improved SCMLI based on NPC structure is proposed to reduce the number of active switches and the number of switches in the charging loop, significantly reducing the power loss. It can generate seven voltage levels with voltage boosting and self-balancing of capacitors within a single-stage power conversion. The working principle of the proposed topology, circuit description, and control technique is presented. Further, the proposed inverter is compared with other recent SC topologies to show its superiority. Finally, a laboratory prototype is developed and tested for the 7-level module under steady-state and dynamic conditions to validate the practical viability of the proposed configuration. The proposed inverter's maximum efficiency is 97.5% at 1.2kW rated power.